Pengaruh Halal Tourism terhadap Kepuasan Wisatawan Yang Berkunjung Ke Pantai Lon Malang di Kabupaten Sampang - Moh. Syamsih; Yustina Chrismardani (Jurnal Kajian Ilmu Manajemen (JKIM), 2022)
This study aims to determine the effect of halal tourism on tourist satisfaction. The research method used is quantitative method with primary data through questionnaires distributed to respondents. The data were analyzed by simple regression test using the SPSS application. The sampling technique in this study used a purposive sampling technique, namely the technique of determining the sample using certain considerations, which then obtained 97 samples. The results showed that halal tourism had a positive and significant effect on the satisfaction of tourists visiting Lon Malang Beach in Sampang Regency.